Antibacterial-waterproof hydrogel biosensor based on conductive spandex fiber net and preparation method of antibacterial-waterproof hydrogel biosensor
By adopting conductive spandex fiber mesh, nanosilver and dual network structures in hydrogel biosensors, the problem of insignificant effects of traditional restorative materials is solved, efficient postoperative rehabilitation monitoring and evaluation is achieved, and scientific rehabilitation guidance is provided.
Patent Information
- Application Number
- CN202411302244.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Traditional nerve injury repair materials are not effective significantly, and it is difficult to meet the real-time monitoring and evaluation needs of postoperative rehabilitation process.
Using an antibacterial-waterproof hydrogel biosensor based on conductive spandex fiber web, the combination of solution dry spinning, nanoblending, in-situ casting and dual network structure was prepared to produce conductive, stretchable, antibacterial and waterproof Functional hydrogel biosensor.
The high conductivity, good mechanical properties and long-term stability of hydrogel biosensors are achieved, and they can monitor patients' rehabilitation movements in real time, provide scientific guidance, and avoid errors and accidents in postoperative rehabilitation.
Smart Images

Figure CN119405299A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation technology of a conductive hydrogel and a biosensor, and in particular to an antibacterial-waterproof hydrogel biosensor based on a conductive spandex fiber net and a preparation method thereof. Background Art
[0002] Limb bones include upper limb bones and lower limb bones, which are composed of limb girdle bones connected to the trunk and free limb bones that move freely. The number and arrangement of upper and lower limb bones are basically the same. The characteristics are that the upper limb bones are light and flexible, and the lower limb bones are thick and solid, which play the role of supporting and moving the body, which is closely related to human upright walking. However, with the development of industry and transportation, the incidence of bone defects and bone injuries in life has increased year by year. After patients undergo orthopedic surgery, they often experience a long recovery period.
[0003] During this recovery period, patients may also lack knowledge of postoperative rehabilitation, which may lead to incorrect / inadequate / overtraining of postoperative rehabilitation training. The above situations will not only fail to promote the patient's recovery, but may even lead to accidents in the bone repair process. Therefore, if the patient's rehabilitation process can be monitored and evaluated in real time, it will provide great help to the patient and can efficiently promote the patient's postoperative rehabilitation work.
[0004] In view of the above problems, a biostrain sensor is a device that can convert its own strain information into biological signals. If it can be used to monitor the rehabilitation behavior of patients after fracture / bone injury surgery, it will be possible to guide the rehabilitation behavior of patients. Therefore, the present invention proposes an antibacterial-waterproof hydrogel biosensor based on a conductive spandex fiber mesh and a preparation method thereof, which is used to deal with common problems in the use of hydrogel biosensors and provide a new auxiliary strategy for postoperative rehabilitation. Summary of the invention
[0005] The purpose of the present invention is to provide an antibacterial-waterproof hydrogel biosensor based on a conductive spandex fiber mesh and a preparation method thereof, in view of the problems that traditional nerve damage repair materials are not effective. The biosensor has the functions of being conductive, stretchable, antibacterial, and waterproof, and can be applied to biological strain monitoring.
[0006] The present invention is implemented by the following technical solution, and the specific steps are as follows:
[0007] A method for preparing an antibacterial-waterproof hydrogel biosensor based on a conductive spandex fiber mesh comprises the following steps:
[0008] 1) preparing graphene composite elastic spandex conductive fibers by solution dry spinning, and weaving the fibers into a fiber web;
[0009] 2) designing a rectangular parallelepiped mold, and fixing the fiber mesh in the rectangular parallelepiped mold as a first layer of conductive fiber mesh structure;
[0010] 3) preparing a sodium alginate / acrylamide mixed solution blended with nano-silver, and pouring the mixed solution into the rectangular parallelepiped mold for in-situ polymerization after centrifugal degassing;
[0011] 4) Transfer the rectangular parallelepiped mold to Ca 2+ Immersing in a coagulation bath to form a second layer of gel matrix structure with a double network;
[0012] 5) demoulding from the rectangular parallelepiped mold, performing gel dialysis, and then immersing it in a stearic acid / organic silicon emulsion / vegetable oil mixed solution for hydrophobic modification to form a third waterproof layer structure on its surface, and finally obtaining a hydrogel biosensor after drying.
[0013] Furthermore, in the process of dry spinning of the solution in step 1), graphene, polyurethane prepolymer, and mixed diamine / diol solution are first prepared, and a chain terminator is added after the reaction to obtain a graphene-compounded spandex stock solution, and the spandex stock solution is spun through a spinning head under pressure, and the spandex is twisted, oiled, and wound under hot air conditions to obtain spandex;
[0014] Furthermore, in the process of preparing the spandex stock solution, the graphene size is 2-4 microns and the concentration is 0.01-0.1wt%; the polyurethane prepolymer is one of polyether, polyester and aliphatic isocyanate, and the concentration is 20-35wt%; the diamine is one of ethylenediamine, propylenediamine and pentamethylenediamine, and the diol is one of propylene glycol and butanediol, and the total concentration of the two is 2-8wt%; the reaction temperature is 60-90°C and the reaction time is 45-60min; the chain terminator is one of ethanolamine, diethanolamine, triethanolamine and N,N-dimethylethanolamine, and the concentration is 0.1-1‰ of the diol;
[0015] During the spinning process, the aperture of the spinning head is about 50-100 microns, and the spinning rate is 50-100 m / s.
[0016] Furthermore, in step 2), a groove is formed in the rectangular mold, and a plurality of hooks are evenly fixed on the inner wall of the groove in the middle position in the depth direction of the groove to fix the fiber mesh, the spacing between adjacent hooks is 0.5-1 cm / piece, and the depth of the rectangular mold is 1-3 mm.
[0017] Further, in step 3), the prepared mixed solution contains a crosslinking agent, an initiator and a polymerization promoter, the size of the nanosilver is 20-50nm, and the addition amount is 0.01-0.05wt%; the viscosity of the sodium alginate is 0.02-0.1Pa·s at 10g / L and 20°C, and the concentration is 3-4wt%; the concentration of the acrylamide is 3-10wt%, the concentration of the crosslinking agent N,N'-methylenebisacrylamide (MBAA) is 0.02-0.10wt%, the initiator is one or more of ammonium persulfate, sodium persulfate, and potassium persulfate, and the concentration is 0.5-0.95wt%, and the polymerization promoter is tetramethylethylenediamine, and the concentration is 0.025-0.08wt%;
[0018] The centrifugal degassing rate is 1000-2000rpm, and the time is 3-8min;
[0019] The in-situ polymerization temperature is 30-35° C. and the time is 4-12 hours.
[0020] Further, in step 4), during the coagulation bath, the Ca 2+ Specifically, it is one or more of calcium chloride, calcium bicarbonate, and calcium gluconate, with a concentration of 5-20wt%, and the immersion time is 30min-4h.
[0021] Further, in step 5), during the preparation of the stearic acid / organic silicon emulsion / vegetable oil mixed solution, the stearic acid concentration is 0.05-0.5 v / v%; the organosilicon is one or more of polydiethylsiloxane, dodecyltriethylsilane, polymethyltrifluoropropylsiloxane, polymethylvinylsiloxane, hexadecyltriethoxysilane, polydimethylsiloxane, hexadecyltrimethoxysilane, methyltriethoxysilane, and the concentration is 1-5 v / v%; the vegetable oil is one or more of olive oil, soybean oil, and sesame oil, and the concentration is 0.5-2 v / v%; the solvent is one of dichloromethane, acetone, trichloroethane, etc.;
[0022] The drying is carried out using nitrogen drying, the time is 6-12 hours, and the temperature is 25-30°C.
[0023] An antibacterial-waterproof hydrogel biosensor based on a conductive spandex fiber mesh is obtained by using any of the above-mentioned preparation methods.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] 1) The present invention uses spandex, graphene, nanosilver, stearic acid, silicone and the like as raw materials, and combines solution dry spinning, nano-blending, in-situ casting, free radical polymerization, physical impregnation cross-linking and other combined processes to prepare an antibacterial-waterproof hydrogel biosensor material based on a conductive spandex fiber mesh. The above raw material selection and process combination are original to the present invention.
[0026] 2) The present invention uses graphene doping and a solution dry spinning process to prepare a conductive spandex composite fiber material, which is woven into a fiber mesh, and the conductive hydrogel material composited with the conductive fiber mesh is prepared in cooperation with a mold and an in-situ casting method. Due to the high elasticity of spandex fiber, after it is compounded in a conductive hydrogel, the tensile properties and tensile strength of the hydrogel can be improved, and its tear resistance can be further improved. This ensures that the integrity of the device is not damaged during use. At the same time, the internally doped graphene has excellent conductive properties, so that the fiber network is enhanced while ensuring the high conductive properties of the material. And due to the stability of graphene, problems such as oxidation of conductive polymers during use can be overcome, and the conductivity will not decay, ensuring the long-term application of conductive hydrogel biosensors.
[0027] 3) The hydrogel biosensor in the present invention is provided with triple reinforcement: the first is spandex fiber mesh reinforcement, the second is nano-silver nano-reinforcement, and the third is double network structure reinforcement. First, a three-layer sandwich fiber network reinforcement structure (a fiber mesh is sandwiched between the upper and lower layers of hydrogel) is formed in the hydrogel by combining the casting method to ensure the elasticity, strength and tear resistance of the hydrogel; secondly, combined with the nano-silver reinforcement technology, the nano-silver adsorbs the sodium alginate and polyacrylamide molecular chains to form physical entanglement points, making the polymer matrix network denser, thereby achieving the purpose of reinforcement; finally, the sodium alginate and polyacrylamide in the hydrogel matrix are in the Ca 2+ Under the physical-chemical cross-linking effects of MBAA, a double network structure is formed to enhance the hydrogel matrix. The synergistic effect of the above multiple enhancements makes the conductive hydrogel in the present invention have good mechanical properties, which can ensure that when monitoring the patient's recovery process in real time, it will not be broken or damaged due to high-frequency and high-frequency stretching, thereby ensuring the stability of the biosensor.
[0028] 4) The hydrogel biosensor in the present invention is provided with a first layer of conductive fiber mesh structure + a second layer of gel matrix structure + a third layer of waterproof layer structure from the inside out, so that it can meet various needs when in use. The first layer of conductive fiber mesh structure ensures the strength, elasticity and conductivity of the hydrogel biosensor; the second layer of gel matrix structure ensures the strength and stability of the material; the third layer of waterproof layer ensures that the biosensor will not swell and reduce the strength of the hydrogel due to water absorption and sweat absorption during use, and ensures the stability and accuracy of the biosensor's transmission of patient rehabilitation movement signals. It is through the synergy between the above-mentioned composite structures that the hydrogel biosensor in the present invention can meet the complex needs of postoperative rehabilitation monitoring of patients.
[0029] 5) The hydrogel biosensor in the present invention has the functions of being conductive, stretchable, antibacterial, and waterproof. The graphene doped in the spandex fiber and the nanosilver nanocomposite in the polymer matrix ensure the excellent conductive properties of the hydrogel; the internal spandex fiber mesh and cross-linked acrylamide ensure the elasticity and recoverability of the hydrogel. Combined with the conductive properties of the hydrogel, when the hydrogel biosensor is stretched with the movement of the patient's limbs during the rehabilitation process, its resistance changes, thereby causing the transmitted electrical signal to change synchronously, and a real-time strain-resistance curve is obtained. The amplitude of the patient's use can be reflected by the change in resistance, thereby achieving real-time monitoring of the patient's motor behavior; and since the patient will sweat and contact external objects during the postoperative rehabilitation process, bacteria will grow on the hydrogel, and it is also possible that the hydrogel absorbs sweat or other liquids, causing the hydrogel to be contaminated or damaged. Therefore, the present invention further introduces nanosilver and hydrophobic stearic acid, silicone and other materials to ensure that the hydrogel will not grow bacteria during use, nor will it absorb water / liquid to swell and be damaged. It is through the coordination of the above functions that the hydrogel biosensor in the present invention can meet complex usage requirements and provide scientific guidance for patients' postoperative rehabilitation. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention is a schematic diagram of the preparation process of the antibacterial-waterproof hydrogel biosensor based on the conductive spandex fiber mesh.
[0031] Figure 2 The contact angle results of the antibacterial-waterproof hydrogel biosensor based on the conductive spandex fiber mesh according to the embodiments of the present invention (A is embodiment 1 and B is embodiment 2);
[0032] Figure 3 These are the inhibition zone results of the antibacterial-waterproof hydrogel biosensor based on the conductive spandex fiber mesh according to the embodiments of the present invention (A is embodiment 1 and B is embodiment 3). DETAILED DESCRIPTION
[0033] The present invention is further described below with reference to specific examples and accompanying drawings.
[0034] Comparative Example 1:
[0035] 1) Design a rectangular parallelepiped mold (a groove structure is provided in the middle of the rectangular parallelepiped mold, and the mold groove is 5 cm long, 1.5 cm wide and 1.5 mm deep. Prepare a mixed solution of sodium alginate (viscosity of 0.02-0.1 Pa·s (10 g / L, 20°C), concentration of 3wt%) and acrylamide (concentration of 5wt%, initiator of ammonium persulfate, concentration of 0.5wt%, crosslinker of MBAA, concentration of 0.05wt%, polymerization promoter of tetramethylethylenediamine, concentration of 0.03wt%) blended with nanosilver (size of about 30 nm, addition amount of 0.05wt%), and cast it into the rectangular parallelepiped mold for in-situ polymerization (in-situ polymerization temperature of 35°C, time of 6h) after low-speed centrifugal degassing (speed of 1000rpm, time of 5min);
[0036] 2) transferring the rectangular parallelepiped mold to a 10 wt% calcium chloride coagulation bath and immersing it for 2 h to form a gel matrix structure with a double network;
[0037] 3) After the gel dialysis is complete, it is immersed in a mixed solution of 0.25v / v% stearic acid / 3v / v% polydiethylsiloxane / 0.5v / v% olive oil (the solvent is dichloromethane) for hydrophobic modification to form a waterproof layer structure on its surface. After completion, it is dried at 25°C in nitrogen for 8 hours to finally obtain a hydrogel biosensor.
[0038] The material antibacterial zone is about 1.14cm 2 The contact angle is about 148°. The tensile strength of the hydrogel was tested using a universal testing machine. When its elongation at break was about 626%, the maximum tensile strength was about 724 kPa. It broke after 5 cycles of stretching at 500% strain. When it was applied to biological strain sensors, there was a linear relationship between the rate of change of resistance and the strain, and it would not grow bacteria or absorb sweat during use.
[0039] Embodiment 1:
[0040] 1) preparing graphene composite elastic spandex conductive fibers by solution dry spinning (first preparing a graphene with a concentration of 0.05 wt% and a size of 2-4 microns, a polyether polyurethane prepolymer with a concentration of 25 wt%, and a mixed ethylenediamine / propylene glycol solution with a concentration of 5 wt%, adding a chain terminator ethanolamine with a content of 0.5‰ of propylene glycol after the reaction to obtain a graphene composite spandex stock solution, spinning the stock solution through a spinning head under pressure, twisting, oiling, and winding under hot air conditions to obtain spandex; wherein the spinning head aperture is about 50 microns, and the spinning rate is 100 m / s) and weaving the graphene composite elastic spandex conductive fibers into a fiber web;
[0041] 2) Design a rectangular mold (a groove structure is set in the middle of the rectangular mold, and a small hook is set at the middle position of the depth direction of the four sides of the groove, that is, 0.75mm from the bottom of the groove, for fixing the fiber mesh. Multiple hooks are set along the length and width of the rectangular mold, with a spacing of 0.5cm / piece. The groove of the rectangular mold is 5cm long, 1.5cm wide and 1.5mm deep. Figure 1 The middle mold is only a schematic diagram), and the fiber mesh is fixed on the hooks on the four sides of the groove of the rectangular mold as the first layer of conductive fiber mesh structure;
[0042] 3) preparing a mixed solution of sodium alginate (viscosity of 0.02-0.1 Pa·s (10 g / L, 20° C.), concentration of 3wt%) and acrylamide (concentration of 5wt%, initiator of ammonium persulfate, concentration of 0.5wt%, crosslinker of MBAA, concentration of 0.05wt%, polymerization promoter of tetramethylethylenediamine, concentration of 0.03wt%) blended with nanosilver (size of about 30 nm, addition amount of 0.05wt%), and casting the mixed solution into a rectangular parallelepiped mold for in-situ polymerization (in-situ polymerization temperature of 35° C., time of 6h) after low-speed centrifugal degassing (speed of 1000 rpm, time of 5min);
[0043] 4) transferring the rectangular parallelepiped mold to a 10 wt% calcium chloride coagulation bath and immersing it for 2 hours to form a second layer of gel matrix structure with a double network;
[0044] 5) After the gel dialysis is complete, it is immersed in a mixed solution of 0.25v / v% stearic acid / 3v / v% polydiethylsiloxane / 0.5v / v% olive oil (the solvent is dichloromethane) for hydrophobic modification to form a third waterproof layer structure on its surface. After completion, it is dried at 25°C in nitrogen for 8 hours to finally obtain an antibacterial-waterproof hydrogel biosensor based on a conductive spandex fiber mesh.
[0045] Compared with comparative example 1, this embodiment adds a conductive spandex fiber mesh structure. The antibacterial zone of the material is about 1.27 cm 2 ,like Figure 3As shown in Example A, the contact angle is about 143°. Figure 2 As shown in Example A; the tensile strength of the hydrogel is tested using a universal testing machine, and when its elongation at break is about 1258%, the maximum tensile strength is about 1.42MPa; it is cyclically stretched 50 times under 500% strain without breaking; when it is applied to a biological strain sensor, there is a linear relationship between its resistance change rate and strain, and it will not grow bacteria or absorb sweat during use.
[0046] Embodiment 2:
[0047] 1) preparing graphene composite elastic spandex conductive fibers by solution dry spinning (first preparing a graphene with a concentration of 0.05 wt% and a size of 2-4 microns, a polyether polyurethane prepolymer with a concentration of 25 wt%, and a mixed ethylenediamine / propylene glycol solution with a concentration of 5 wt%, adding a chain terminator ethanolamine with a content of 0.5‰ of propylene glycol after the reaction to obtain a graphene composite spandex stock solution, spinning the stock solution through a spinning head under pressure, twisting, oiling, and winding under hot air conditions to obtain spandex; wherein the spinning head aperture is about 50 microns, and the spinning rate is 100 m / s) and weaving the graphene composite elastic spandex conductive fibers into a fiber web;
[0048] 2) Design a rectangular mold (a groove structure is provided in the middle of the rectangular mold, and small hooks are provided in the middle of the longitudinal direction, i.e., the depth direction, of the four sides of the groove to fix the fiber mesh. Several hooks can be provided along the length and width of the mold, with a spacing of 0.5 cm / piece. The mold groove is 5 cm long, 1.5 cm wide, and 1.5 mm deep), and the fiber mesh is fixed on the hooks on the four sides of the groove of the rectangular mold as the first layer of the conductive fiber mesh structure;
[0049] 3) preparing a mixed solution of sodium alginate (viscosity of 0.02-0.1 Pa·s (10 g / L, 20° C.), concentration of 3wt%) and acrylamide (concentration of 5wt%, initiator of ammonium persulfate, concentration of 0.5wt%, crosslinker of MBAA, concentration of 0.05wt%, polymerization promoter of tetramethylethylenediamine, concentration of 0.03wt%) blended with nanosilver (size of about 30 nm, addition amount of 0.05wt%), and casting the mixed solution into a rectangular parallelepiped mold for in-situ polymerization (in-situ polymerization temperature of 35° C., time of 6h) after low-speed centrifugal degassing (speed of 1000 rpm, time of 5min);
[0050] 4) The rectangular mold was transferred to a 10 wt% calcium chloride coagulation bath and immersed for 2 h to form a second layer of gel matrix structure with a double network. After dialysis and drying, the desired hydrogel biosensor was finally obtained.
[0051] Compared with Example 1, the third waterproof layer is omitted in this embodiment. The antibacterial zone of the material is about 2.98 cm 2 ; The contact angle is about 22°, such as Figure 2 As shown in the negative control of B; the tensile strength of the hydrogel was tested using a universal testing machine, and when its elongation at break was about 1344%, the maximum tensile strength was about 1.28MPa; it was stretched 50 times under 500% strain without breaking; when it was applied to a biological strain sensor, there was a linear relationship between its resistance change rate and strain, and it would not grow bacteria during use, but it would absorb sweat and partially swell. After swelling, the resistance change rate and strain curve changed, affecting the monitoring results.
[0052] Embodiment 3:
[0053] 1) preparing graphene composite elastic spandex conductive fibers by solution dry spinning (first preparing a graphene with a concentration of 0.05 wt% and a size of 2-4 microns, a polyether polyurethane prepolymer with a concentration of 25 wt%, and a mixed ethylenediamine / propylene glycol solution with a concentration of 5 wt%, adding a chain terminator ethanolamine with a content of 0.5‰ of propylene glycol after the reaction to obtain a graphene composite spandex stock solution, spinning the stock solution through a spinning head under pressure, twisting, oiling, and winding under hot air conditions to obtain spandex; wherein the spinning head aperture is about 50 microns, and the spinning rate is 100 m / s) and weaving the graphene composite elastic spandex conductive fibers into a fiber web;
[0054] 2) Design a rectangular mold (a groove structure is provided in the middle of the rectangular mold, and small hooks are provided in the middle of the longitudinal direction, i.e., the depth direction, of the four sides of the groove for fixing the fiber mesh. Several hooks are provided in the length and width directions, and the lateral spacing of the hooks is 0.5 cm / piece. The mold groove is 5 cm long, 1.5 cm wide, and 1.5 mm deep), and the fiber mesh is fixed on the hooks on the four sides of the groove of the rectangular mold as the first layer of the conductive fiber mesh structure;
[0055] 3) preparing a mixed solution of sodium alginate (viscosity of 0.02-0.1 Pa·s (10 g / L, 20°C), concentration of 3 wt%) / acrylamide (concentration of 5 wt%, initiator of ammonium persulfate, concentration of 0.5 wt%, cross-linking agent of MBAA, concentration of 0.05 wt%, polymerization promoter of tetramethylethylenediamine, concentration of 0.03 wt%), degassing by low-speed centrifugation (rate of 1000 rpm, time of 5 min), and then pouring the mixed solution into a rectangular parallelepiped mold for in-situ polymerization (in-situ polymerization temperature of 35°C, time of 6 h);
[0056] 4) transferring the rectangular parallelepiped mold to a 10 wt% calcium chloride coagulation bath and immersing it for 2 hours to form a second layer of gel matrix structure with a double network;
[0057] 5) After the gel dialysis is complete, it is immersed in a mixed solution of 0.25v / v% stearic acid / 3v / v% polydiethylsiloxane / 0.5v / v% olive oil (the solvent is dichloromethane) for hydrophobic modification to form a third waterproof layer structure on its surface. After completion, it is dried at 25°C in nitrogen for 8 hours to finally obtain a hydrogel biosensor.
[0058] Compared with Example 1, this example reduces the addition of nanosilver. The material has no inhibition zone, such as Figure 3 As shown in the negative control of B; the contact angle is about 153°; the tensile strength of the hydrogel is tested using a universal testing machine, and when its elongation at break is about 1368%, the maximum tensile strength is about 988kPa; it is stretched 50 times under 500% strain without breaking; when it is applied to biological strain sensors, there is a linear relationship between the resistance change rate and the strain, and it will not absorb sweat during use, but mildew will appear on the surface of the gel after a few days of use.
Claims
1. A method for preparing an antibacterial-waterproof hydrogel biosensor based on a conductive spandex fiber mesh, characterized in that: The following steps are involved: 1) preparing graphene composite elastic spandex conductive fibers by solution dry spinning, and weaving the fibers into a fiber web; 2) designing a rectangular parallelepiped mold, and fixing the fiber mesh in the rectangular parallelepiped mold as a first layer of conductive fiber mesh structure; 3) preparing a sodium alginate / acrylamide mixed solution blended with nano-silver, and pouring the mixed solution into the rectangular parallelepiped mold for in-situ polymerization after centrifugal degassing; 4) Transfer the rectangular parallelepiped mold to Ca 2+ Immersing in a coagulation bath to form a second layer of gel matrix structure with a double network; 5) demoulding from the rectangular parallelepiped mold, performing gel dialysis, and then immersing it in a stearic acid / organic silicon emulsion / vegetable oil mixed solution for hydrophobic modification to form a third waterproof layer structure on its surface, and finally obtaining a hydrogel biosensor after drying.
2. The method for preparing the antibacterial-waterproof hydrogel biosensor based on the conductive spandex fiber mesh according to claim 1, characterized in that: In the process of dry spinning of the solution in step 1), graphene, polyurethane prepolymer and mixed diamine / diol solution are first prepared, and a chain terminator is added after the reaction to obtain a graphene-compounded spandex stock solution, and the spandex stock solution is spun through a spinning head under pressure, and spandex is obtained after twisting, oiling and winding under hot air conditions.
3. The method for preparing the antibacterial-waterproof hydrogel biosensor based on conductive spandex fiber mesh according to claim 2, characterized in that: During the preparation of the spandex stock solution, the graphene has a size of 2-4 microns and a concentration of 0.01-0.1wt%; the polyurethane prepolymer is one of polyethers, polyesters, and aliphatic isocyanates, and the concentration is 20-35wt%; the diamine is one of ethylenediamine, propylenediamine, and pentamethylenediamine; the diol is one of propylene glycol and butanediol, and the total concentration of the two is 2-8wt%; the reaction temperature is 60-90°C, and the reaction time is 45-60min; the chain terminator is one of ethanolamine, diethanolamine, triethanolamine, and N,N-dimethylethanolamine, and the concentration is 0.1-1‰ of the diol; During the spinning process, the aperture of the spinning head is about 50-100 microns, and the spinning rate is 50-100 m / s.
4. The method for preparing the antibacterial-waterproof hydrogel biosensor based on conductive spandex fiber mesh according to claim 1, characterized in that: In step 2), a groove is formed in the rectangular mold, and a plurality of hooks are evenly fixed on the inner wall of the groove in the middle position in the depth direction of the groove to fix the fiber mesh, the spacing between adjacent hooks is 0.5-1 cm / piece, and the depth of the rectangular mold is 1-3 mm.
5. The method for preparing the antibacterial-waterproof hydrogel biosensor based on conductive spandex fiber mesh according to claim 1, characterized in that: In step 3), the prepared mixed solution contains a crosslinking agent, an initiator and a polymerization promoter, the size of the nanosilver is 20-50nm, and the addition amount is 0.01-0.05wt%; the viscosity of the sodium alginate is 0.02-0.1Pa·s at 10g / L and 20°C, and the concentration is 3-4wt%; the concentration of the acrylamide is 3-10wt%, the concentration of the crosslinking agent N,N′-methylenebisacrylamide (MBAA) is 0.02-0.10wt%, the initiator is one or more of ammonium persulfate, sodium persulfate, and potassium persulfate, and the concentration is 0.5-0.95wt%, and the polymerization promoter is tetramethylethylenediamine, and the concentration is 0.025-0.08wt%; The centrifugal degassing rate is 1000-2000rpm, and the time is 3-8min The in-situ polymerization temperature is 30-35° C. and the time is 4-12 hours.
6. The method for preparing the antibacterial-waterproof hydrogel biosensor based on conductive spandex fiber mesh according to claim 1, characterized in that: In step 4), during the coagulation bath, the Ca 2+ Specifically, it is one or more of calcium chloride, calcium bicarbonate, and calcium gluconate, with a concentration of 5-20wt%, and the immersion time is 30min-4h.
7. The method for preparing the antibacterial-waterproof hydrogel biosensor based on conductive spandex fiber mesh according to claim 1, characterized in that: In step 5), during the preparation of the stearic acid / organic silicon emulsion / vegetable oil mixed solution, the stearic acid concentration is 0.05-0.5 v / v%; the organosilicon is one or more of polydiethylsiloxane, dodecyltriethylsilane, polymethyltrifluoropropylsiloxane, polymethylvinylsiloxane, hexadecyltriethoxysilane, polydimethylsiloxane, hexadecyltrimethoxysilane, methyltriethoxysilane, and the concentration is 1-5 v / v%; the vegetable oil is one or more of olive oil, soybean oil, and sesame oil, and the concentration is 0.5-2 v / v%; the solvent is one of dichloromethane, acetone, trichloroethane, etc.; The drying is carried out using nitrogen drying, the time is 6-12 hours, and the temperature is 25-30°C.
8. An antibacterial-waterproof hydrogel biosensor based on a conductive spandex fiber mesh, characterized in that: The method is adopted as described in any one of claims 1 to 7.
Citation Information
Patent Citations
Superfine graphene fibers and method for preparing same
CN105648579A
Flexible strain sensor based on conductive hydrogel and preparation method and application thereof
CN116183071A
Method for manufacturing stretchable wiring structures consisting of coil-shaped conductors and stretchable wiring structures manufactured thereof
KR1020170124828A
Piezoresponsive textile incorporating graphene
US20200011006A1
Three-dimensional hydrogel-graphene-based biosensor and preparation method therefor
WO2022262014A1
Cited By
Small-scale test preparation method of conductive polyurethane fiber
CN122522446A